Age Differences in Negative, but Not Positive, Rumination. (26th August 2019) - Emery, Lisa; Sorrell, Anne; Miles, Cassidy
Abstract: Objectives: The main objective of this study was to determine whether there are age differences in positive and negative repetitive thought (ie, rumination). Method: Young adults (ages 19–39; n = 114) and older adults (ages 60–85; n = 88) completed measures of negative and positive rumination. Bayesian analyses were used to determine whether age differences were present for both negative (young > old) and positive (old > young) rumination. Results: There was extremely strong evidence for age differences in negative rumination, with lower scores in older adults. In contrast, the evidence was in favor of the null hypothesis for positive rumination. Discussion: Age-related positivity is better characterized as decreased dwelling on the meaning of negative moods, rather than increased attention to positive ones.